Composite nickel-based alloy microchannel and preparation method thereof

By doping silicon powder in the nickel-based alloy microchannel and heat treatment, the composite nickel-based alloy microchannel is formed, which solves the problems of corrosion resistance and molding quality in the prior art, and achieves high density and acid corrosion resistance The improvement is suitable for micro-reactor equipment in acidic environments.

CN119216585AActive Publication Date: 2024-12-31GUANGDONG INST OF NEW MATERIALS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411340065.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The corrosion resistance of existing 3D printed microchannels is insufficient, especially in acidic environments, and the molding quality is poor, which is prone to cracks and pore problems.

Method used

By doping silicon powder and heat treatment, composite nickel-based alloy microchannels are formed, using the covalent bond and metal bond characteristics of silicon elements to improve corrosion resistance, and 3D printing technology achieves high density and good molding quality to avoid cracks and the generation of stomata.

Benefits of technology

It significantly improves the acid corrosion resistance and molding quality of the composite nickel-based alloy microchannel, ensures stability and durability in an acidic environment, avoids pitting problems, and is suitable for core parts of chemical equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119216585A_ABST
    Figure CN119216585A_ABST
Patent Text Reader

Abstract

The invention provides a composite nickel-based alloy microchannel and a preparation method thereof, and the preparation method comprises the following steps: S1, preparing nickel-based alloy powder which comprises the following element components in percentage by mass: 15-20% of Cr, 16-20% of Mo, 0.5-1% of Mn, 2-3% of W and 54-62.5% of Ni for later use; s2, 2-3% of silicon powder is doped into the nickel-based alloy powder obtained in the S1, ball milling mixing is conducted, grinding balls are not added in the ball milling process, and nickel-based alloy composite powder is obtained for standby application; and S3, preheating is conducted, specifically, the nickel-based alloy composite powder obtained in S2 is prepared through 3D printing to obtain a target, annealing treatment is conducted at the temperature of 600-780 DEG C, furnace cooling is conducted, and the composite nickel-based alloy microchannel is obtained. The composite nickel-based alloy micro-channel prepared through the operation of element selection and independent doping of the silicon powder is excellent in 3D printing forming quality, free of cracks, high in density, few in air holes, high in density, good in corrosion resistance and good in forming quality, and the problems that in the prior art, materials are poor in corrosion resistance and poor in forming quality can be effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal additive manufacturing, and in particular to a composite nickel-based alloy microchannel and a preparation method thereof. Background Art

[0002] A microchannel, also known as a microchannel reactor, is a three-dimensional structural unit made of a solid matrix that can be used for chemical reactions. This type of reactor has an equivalent diameter of a fluid channel of only a few microns or a few hundred microns. It contains numerous microchannels, greatly reduces the thickness of the moving boundary layer, and greatly shortens the average heat and mass diffusion distance. This allows the fluid in the microchannel to flow in a combined manner in the reactor in a specific physical state, achieving efficient mass and heat transfer between fluids, and utilizing the inherent characteristics of rapid surface reaction kinetics to achieve process intensification of chemical reactions, greatly increasing the reaction rate.

[0003] In the manufacturing technology of metal microchannel reactors, the traditional manufacturing method is to first use mechanical processing, and then bolt press or diffusion welding to obtain a formed microchannel, but there are too many welding surfaces, poor pressure bearing capacity, and a great risk of leakage. In 2019, China's patent CN110935407A "A microchannel reactor and its manufacturing method" for the first time produced a 3D printed microchannel with a large liquid holding capacity. Its special molding method is different from the traditional processing method. It has the advantages of one-piece molding, high space utilization, high density, and low cost. It can produce structures that are difficult to manufacture by traditional processing methods. 3D printed microchannels are a revolutionary alternative technology that is likely to replace traditional chemical equipment because of their safety, high efficiency, and green energy saving.

[0004] However, due to the high specific surface area and small characteristic size of the microchannel, even a very small corrosion degradation will have a significant impact on the microchannel, which makes the microchannel have very high anti-corrosion requirements for the material. At present, the raw materials used in 3D printing microchannels are mainly pure tantalum, nickel-based high-temperature alloys, Hastelloy, and stainless steel. Ordinary nickel-based alloys or stainless steel are difficult to cope with strong acid corrosion environments such as hydrofluoric acid for a long time, and the price of pure tantalum that can be tolerated is very expensive. It is not practical to use pure tantalum to produce microchannel reactors. Although Hastelloy has good corrosion resistance, it is difficult to maintain stability under long-term acidic liquid erosion, especially in an environment above 50°C. As the core parts of the microreactor and the core equipment of the microreactor, it is necessary to develop a material with higher corrosion resistance.

[0005] Chinese patent CN117643849A "A microchannel reactor and its manufacturing method" discloses a 3D printed microchannel, which uses bimetallic materials to manufacture an ABA sandwich structure. Only the middle sandwich structure uses highly corrosion-resistant B material to reduce the overall cost of the microchannel reactor. However, the patent does not study the corrosion resistance of the microchannel material.

[0006] Therefore, it is of great significance to develop a composite nickel-based alloy microchannel that is uniformly formed and can improve the comprehensive performance of the composite nickel-based alloy microchannel, as well as a preparation method and application thereof. Summary of the invention

[0007] In view of the problem that the corrosion resistance of existing 3D printed microchannels still needs to be further improved, the present invention provides a composite nickel-based alloy microchannel and a preparation method thereof, which introduces partial covalent bonds by doping silicon powder, and evenly diffuses silicon elements to the entire metal by heat treatment, thereby comprehensively enhancing the corrosion resistance of the microchannel. The obtained composite nickel-based alloy microchannel has good 3D printing molding, no cracks, high density, few pores, high density, good corrosion resistance and good molding quality, and can effectively avoid the problems of poor corrosion resistance and poor molding quality of existing technologies and materials.

[0008] To achieve the above object, the technical solution adopted by the present invention is:

[0009] A method for preparing a composite nickel-based alloy microchannel comprises the following steps:

[0010] S1. Prepare a nickel-based alloy powder, comprising the following elements by mass percentage: Cr: 15-20%, Mo: 16-20%, Mn: 0.5-1%, W: 2-3%, Ni: 54-62.5%, for standby use;

[0011] S2. The nickel-based alloy powder is doped with 2-3% silicon powder in S1, and the mixture is ball-milled without adding grinding balls during the ball milling process to obtain a nickel-based alloy composite powder for use;

[0012] S3. Preheating, using 3D printing to prepare the nickel-based alloy composite powder of S2 to obtain the target, annealing at 600-780°C, and cooling with the furnace to obtain the composite nickel-based alloy microchannel;

[0013] The particle size of the nickel-based alloy powder in S1 is 15-53 μm, and the sphericity is ≥ 90%. The particle size of the silicon powder in S2 is 5-15 μm, and the sphericity is ≥ 80%.

[0014] S3 The 3D printing laser power is 250-450w, the speed is 600-1000mm / s, and the powder thickness is 40-60μm.

[0015] The existing corroded pipeline materials for chemical transportation are difficult to maintain long-term safe transportation. Therefore, the pipelines are updated with new materials during annual maintenance. However, microchannels, as core components of key chemical equipment, are difficult to meet the annual replacement requirements due to value, material and other issues. The failure of microchannels is often caused by microscopic pitting, and pitting often occurs first in the grain boundaries.

[0016] In view of this, the present application creatively proposes a method for preparing a composite nickel-based alloy microchannel, by compounding silicon powder and nickel-based alloy powder according to the ratio provided in the present application, 3D printing is used to obtain a composite nickel-based alloy microchannel, partial covalent bonds are introduced by doping silicon powder, and the silicon element is evenly diffused throughout the metal by heat treatment. During the 3D printing process, the nickel-based alloy powder melts and solidifies, and generally the boundary of the nickel-based alloy powder melts and forms a eutectic structure with the silicon powder, existing in the form of a mixture, thereby comprehensively enhancing the corrosion resistance of the composite nickel-based alloy microchannel, reducing the stress of the composite nickel-based alloy microchannel, and preventing the occurrence of cracks.

[0017] When the silicon powder content exceeds 3%, the composite nickel-based alloy microchannel is prone to cracks. When it exceeds 5%, the 3D printed sample will inevitably crack. The reason is that excessive silicon powder can easily break the balance of the alloy elements, causing the FCC phase to transform into the BCC phase in the composite nickel-based alloy microchannel, and unmelted silicon particles will appear, causing cracks.

[0018] In the present application, the preferred nickel-based alloy powder particle size is 15-53μm, and the sphericity is ≥90%, and the preferred silicon powder particle size is 5-15μm, and the sphericity is ≥80%, which can ensure that the silicon powder is effectively retained in the gaps of the nickel-based alloy powder through ball milling, so that the silicon powder and the nickel-based alloy powder are fully mixed, and the silicon powder segregation during the 3D printing process is avoided, which causes defects in the composite nickel-based alloy microchannel, ensures the formation of a good eutectic structure, and improves the molding quality of the composite nickel-based alloy microchannel. If the silicon powder particle size is too small or the nickel-based alloy powder particle size is too large, the silicon powder will not be able to be well mixed with the nickel-based alloy powder, and the silicon powder may be segregated during the printing process. Similarly, if the silicon powder particle size is too large or the nickel-based alloy powder particle size is too small, it will be difficult to form a good eutectic structure, affecting the molding quality.

[0019] In the present application, it is preferred that no grinding balls are added during the ball milling process. If grinding balls are added, the mixed silicon powder may be broken into nano powders, so that the silicon powder particle size cannot be well matched with the nickel-based alloy powder, resulting in defects in the composite nickel-based alloy microchannel.

[0020] In this application, the preferred 3D printing laser power is 250-450w, the speed is 600-1000mm / s, and the powder thickness is 40-60μm. If the laser power is less than 250w, the laser energy input is low, and the powder melting is not complete. If the laser power exceeds 450w, it is easy to cause element burnout; the scanning speed is lower than 600mm / s, the energy input time is long, and voids are prone to occur; the scanning speed is higher than 1000mm / s, the energy input time is short, and the powder is prone to unmelted phenomenon; if the powder thickness is lower than 40μm, powder jamming is prone to occur, and the powder cannot be evenly spread; if the powder spraying thickness is higher than 60 microns, the powder is prone to sintering.

[0021] In the present application, it is preferred that 3D printing also includes an annealing step immediately after printing is completed. Annealing can better promote the solid solution of the metal, increase the corrosion resistance of the metal, eliminate stress, and reduce the chance of cracking. If the annealing temperature is lower than 600°C, it is easy to cause the solid solution of silicon element to be unclear and the corrosion resistance to be improved. If it is higher than 780°C, it is easy to cause changes in the coating structure and performance.

[0022] Furthermore, the nickel-based alloy powder described in S1 has a median particle size of 30-35 μm and a fluidity of 15-20 s / 50 g.

[0023] Furthermore, the nickel-based alloy powder described in S1 is prepared by the following preparation method:

[0024] The required metal elements are mixed in proportion, placed in a smelting furnace, and repeatedly smelted and stirred in a vacuum for 3 times to obtain a nickel-based alloy ingot, which is then powdered by gas atomization to obtain the nickel-based alloy powder.

[0025] Furthermore, the purity of the metal element is greater than 99.7% and the particle size is 0.5-3 mm.

[0026] Furthermore, the median particle size of the silicon powder in S2 is about 8-10 μm.

[0027] Furthermore, the ball milling mixing time in S2 is 60-180 min.

[0028] Furthermore, the 3D printing in S3 is to deposit the nickel-based alloy composite powder on the steel plate by using 3D printing.

[0029] Furthermore, the steel plate is made of No. 45 steel.

[0030] Furthermore, the preheating temperature in S3 is 200-300°C.

[0031] Furthermore, the annealing treatment in S3 is carried out at 600-780° C. for 60-240 min.

[0032] Another object of the present invention is to provide a composite nickel-based alloy microchannel.

[0033] A composite nickel-based alloy microchannel is prepared by any of the composite nickel-based alloy microchannel preparation methods described above.

[0034] Furthermore, the microchannel has an FCC phase.

[0035] Furthermore, the microchannel has an elliptical series structure.

[0036] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0037] The present application obtains a composite nickel-based alloy microchannel by compounding a nickel-based alloy with silicon, wherein the added Cr, Mo, and Si can effectively improve the acid corrosion resistance of the nickel-based alloy, wherein Cr and Mo can significantly improve the acid corrosion of Ni, and the solid solution property of Si, which has a strong interatomic bonding force with the alloy, has the characteristics of coexistence of covalent bonds and metallic bonds. The main functions of Si and W are to improve the hardness and strength of the alloy, wherein Si, in addition to increasing corrosion resistance, also has the effect of increasing hardness, while W can reduce the elongation of the alloy to a small extent, while improving the strength limit and yield point of the alloy, and can also improve the hardness and wear resistance of the alloy. In addition to the above gain effect, Cr, Mo, and Mn are similar to the atomic diameter of Ni, effectively promoting lattice distortion, and can alleviate the brittleness problem caused by Si and W.

[0038] In the present application, silicon is doped into a composite nickel-based alloy microchannel by doping silicon powder alone, so as to avoid the problem of cracks that cannot be solved by heating due to the large stress during the printing process when silicon is doped with nickel-based alloy powder in the form of an alloy, and the forming quality of the composite nickel-based alloy microchannel cannot be guaranteed. By doping small-particle silicon powder alone, the silicon powder is distributed in the gaps of the nickel-based alloy powder during the printing process, so that as little silicon as possible is dissolved into the grains during the printing process, and most of it remains in the grain boundaries in the form of eutectics, thereby reducing the generation of cracks. Subsequently, the silicon element is evenly diffused throughout the entire composite nickel-based alloy microchannel by heat treatment, so as to comprehensively enhance the corrosion resistance and obtain a composite nickel-based alloy microchannel with excellent forming quality and good corrosion resistance.

[0039] The composite nickel-based alloy microchannel provided in the present application has excellent 3D printing molding quality, no cracks, high density, and few pores, which can effectively avoid cracks and pores caused by printing quality. At the same time, heat treatment makes the distribution of various elements more uniform, effectively avoiding the problem of pitting corrosion, and the corrosion resistance is further improved. It can be used for microreactor equipment in acidic corrosive environments and has broad economic value in the future. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] The invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.

[0041] Figure 1 This is a microstructure diagram of the composite nickel-based alloy microchannel of Example 1 of the present application.

[0042] Figure 2 This is a macroscopic image of a composite nickel-based alloy sample prepared by the method for preparing a composite nickel-based alloy microchannel of the present application.

[0043] Figure 3 This is a microstructure diagram of the composite nickel-based alloy microchannel in Example 1 of the present application after being immersed in a mixed acid for 60 days.

[0044] Figure 4 This is a picture of the composite nickel-based alloy microchannel sample of Example 1 of the present application. DETAILED DESCRIPTION

[0045] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention is further described by the following examples. Obviously, the following examples are only part of the embodiments of the present invention, rather than all the embodiments; it should be understood that the embodiments of the present invention are only used to illustrate the technical effects of the present invention, rather than to limit the scope of protection of the present invention.

[0046] The raw materials in the examples can all be obtained commercially; unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0047] Example 1

[0048] A method for preparing a composite nickel-based alloy microchannel comprises the following steps:

[0049] S1. Prepare nickel-based alloy powder, which includes the following elements by mass percentage: Cr: 15%, Mo: 20%, Mn: 0.5%, W: 2%, Ni: 62.5%, for standby use; the sphericity of the nickel-based alloy powder is ≥ 90%, the particle size distribution is 20-50μm, the median particle size is 30-35μm, and the fluidity is 17s / 50g;

[0050] S2. The nickel-based alloy powder described in S1 is doped with 2% silicon powder, placed in a planetary ball mill, and ball-milled for 80 minutes without adding grinding balls during the ball milling process to obtain a nickel-based alloy composite powder for standby use; the sphericity of the silicon powder is ≥80%, the particle size distribution is 5-15μm, the median particle size is 8-10μm, and the fluidity is 25s / 50g;

[0051] S3. Place the No. 45 steel plate in the forming bin, grind the surface of the steel plate flat, and wipe it clean with alcohol; add the mixed nickel-based alloy composite powder into the powder bin, preheat it at 240°C, and use 3D printing to prepare the nickel-based alloy composite powder described in S2 to obtain the target. The process parameters of 3D printing are as follows: laser power is 400W, scanning speed is 850mm / s, powder thickness is 50μm, and after 3D printing, annealing treatment is carried out at 700°C for 120min, and then cooled in the furnace to obtain the composite nickel-based alloy microchannel.

[0052] Example 2

[0053] A method for preparing a composite nickel-based alloy microchannel comprises the following steps:

[0054] S1. Prepare nickel-based alloy powder, which includes the following elements by mass percentage: Cr: 15%, Mo: 20%, Mn: 0.5%, W: 2%, Ni: 62.5%, for standby use; the sphericity of the nickel-based alloy powder is ≥ 90%, the particle size distribution is 20-50μm, the median particle size is 30-35μm, and the fluidity is 17s / 50g;

[0055] S2. The nickel-based alloy powder described in S1 is doped with 3% silicon powder, placed in a planetary ball mill, and ball-milled for 80 minutes without adding grinding balls during the ball milling process to obtain a nickel-based alloy composite powder for standby use; the sphericity of the silicon powder is ≥80%, the particle size distribution is 5-15μm, the median particle size is 8-10μm, and the fluidity is 25s / 50g;

[0056] S3. Place the No. 45 steel plate in the forming bin, grind the surface of the steel plate flat, and wipe it clean with alcohol; add the mixed nickel-based alloy composite powder into the powder bin, preheat it at 240°C, and use 3D printing to prepare the nickel-based alloy composite powder described in S2 to obtain the target. The process parameters of 3D printing are as follows: laser power is 400W, scanning speed is 850mm / s, powder thickness is 50μm, and after 3D printing, annealing treatment is carried out at 700°C for 120min, and then cooled in the furnace to obtain the composite nickel-based alloy microchannel.

[0057] Compared with Example 1, the main difference of this example is that the doping amount of silicon powder in step S2 is 3%.

[0058] Example 3

[0059] A method for preparing a composite nickel-based alloy microchannel comprises the following steps:

[0060] S1. Prepare nickel-based alloy powder, which includes the following elements by mass percentage: Cr: 15%, Mo: 20%, Mn: 0.5%, W: 2%, Ni: 62.5%, for standby use; the sphericity of the nickel-based alloy powder is ≥ 90%, the particle size distribution is 20-50μm, the median particle size is 30-35μm, and the fluidity is 17s / 50g;

[0061] S2. The nickel-based alloy powder described in S1 is doped with 2.5% silicon powder, placed in a planetary ball mill, and ball-milled for 80 minutes without adding grinding balls during the ball milling process to obtain a nickel-based alloy composite powder for standby use; the sphericity of the silicon powder is ≥80%, the particle size distribution is 5-15μm, the median particle size is 8-10μm, and the fluidity is 25s / 50g;

[0062] S3. Place the No. 45 steel plate in the forming bin, grind the surface of the steel plate flat, and wipe it clean with alcohol; add the mixed nickel-based alloy composite powder into the powder bin, preheat it at 240°C, and use 3D printing to prepare the nickel-based alloy composite powder described in S2 to obtain the target. The process parameters of 3D printing are as follows: laser power is 400W, scanning speed is 850mm / s, powder thickness is 50μm, and after 3D printing, annealing treatment is carried out at 700°C for 120min, and then cooled in the furnace to obtain the composite nickel-based alloy microchannel.

[0063] Compared with Example 1, the main difference of this example is that the doping amount of silicon powder in step S2 is 2.5%.

[0064] Example 4

[0065] A method for preparing a composite nickel-based alloy microchannel comprises the following steps:

[0066] S1. Prepare nickel-based alloy powder, which includes the following elements by mass percentage: Cr: 15%, Mo: 20%, Mn: 0.5%, W: 2%, Ni: 62.5%, for standby use; the sphericity of the nickel-based alloy powder is ≥ 90%, the particle size distribution is 20-50μm, the median particle size is 30-35μm, and the fluidity is 17s / 50g;

[0067] S2. The nickel-based alloy powder described in S1 is doped with 2% silicon powder, placed in a planetary ball mill, and ball-milled for 80 minutes without adding grinding balls during the ball milling process to obtain a nickel-based alloy composite powder for standby use; the sphericity of the silicon powder is ≥80%, the particle size distribution is 5-15μm, the median particle size is 8-10μm, and the fluidity is 25s / 50g;

[0068] S3. Place the No. 45 steel plate in the forming bin, grind the surface of the steel plate flat, and wipe it clean with alcohol; add the mixed nickel-based alloy composite powder into the powder bin, preheat it at 240°C, and use 3D printing to prepare the nickel-based alloy composite powder described in S2 to obtain the target. The process parameters of 3D printing are as follows: laser power is 450W, scanning speed is 850mm / s, powder thickness is 50μm, and after 3D printing, annealing treatment is carried out at 700°C for 120min, and then cooled in the furnace to obtain the composite nickel-based alloy microchannel.

[0069] Compared with Example 1, the main difference of this embodiment is that the laser power in step S3 is 450W.

[0070] Example 5

[0071] A method for preparing a composite nickel-based alloy microchannel comprises the following steps:

[0072] S1. Prepare nickel-based alloy powder, which includes the following elements by mass percentage: Cr: 15%, Mo: 20%, Mn: 0.5%, W: 2%, Ni: 62.5%, for standby use; the sphericity of the nickel-based alloy powder is ≥ 90%, the particle size distribution is 20-50μm, the median particle size is 30-35μm, and the fluidity is 17s / 50g;

[0073] S2. The nickel-based alloy powder described in S1 is doped with 2% silicon powder, placed in a planetary ball mill, and ball-milled for 80 minutes without adding grinding balls during the ball milling process to obtain a nickel-based alloy composite powder for standby use; the sphericity of the silicon powder is ≥80%, the particle size distribution is 5-15μm, the median particle size is 8-10μm, and the fluidity is 25s / 50g;

[0074] S3. Place the No. 45 steel plate in the forming bin, grind the surface of the steel plate flat, and wipe it clean with alcohol; add the mixed nickel-based alloy composite powder into the powder bin, preheat it at 240°C, and use 3D printing to prepare the nickel-based alloy composite powder described in S2 to obtain the target. The process parameters of 3D printing are as follows: laser power is 500W, scanning speed is 850mm / s, powder thickness is 50μm, and after 3D printing, annealing treatment is carried out at 700°C for 120min, and then cooled in the furnace to obtain the composite nickel-based alloy microchannel.

[0075] Compared with Example 1, the main difference of this embodiment is that the laser power in step S3 is 500W.

[0076] Example 6

[0077] A method for preparing a composite nickel-based alloy microchannel comprises the following steps:

[0078] S1. Prepare nickel-based alloy powder, which includes the following elements by mass percentage: Cr: 15%, Mo: 20%, Mn: 0.5%, W: 2%, Ni: 62.5%, for standby use; the sphericity of the nickel-based alloy powder is ≥ 90%, the particle size distribution is 20-50μm, the median particle size is 30-35μm, and the fluidity is 17s / 50g;

[0079] S2. The nickel-based alloy powder described in S1 is doped with 2% silicon powder, placed in a planetary ball mill, and ball-milled for 80 minutes without adding grinding balls during the ball milling process to obtain a nickel-based alloy composite powder for standby use; the sphericity of the silicon powder is ≥80%, the particle size distribution is 5-15μm, the median particle size is 8-10μm, and the fluidity is 25s / 50g;

[0080] S3. Place the No. 45 steel plate in the forming bin, grind the surface of the steel plate flat, and wipe it clean with alcohol; add the mixed nickel-based alloy composite powder into the powder bin, preheat it at 240°C, and use 3D printing to prepare the nickel-based alloy composite powder described in S2 to obtain the target. The process parameters of 3D printing are as follows: laser power is 400W, scanning speed is 850mm / s, powder thickness is 50μm, and after 3D printing, annealing treatment is carried out at 750°C for 150min, and then cooled in the furnace to obtain the composite nickel-based alloy microchannel.

[0081] Compared with Example 1, the main difference of this example is that the annealing treatment in step S3 is carried out at 750° C. for 150 min.

[0082] Example 7

[0083] A method for preparing a composite nickel-based alloy microchannel comprises the following steps:

[0084] S1. Prepare nickel-based alloy powder, which includes the following elements by mass percentage: Cr: 15%, Mo: 20%, Mn: 0.5%, W: 2%, Ni: 62.5%, for standby use; the sphericity of the nickel-based alloy powder is ≥ 90%, the particle size distribution is 20-50μm, the median particle size is 30-35μm, and the fluidity is 17s / 50g;

[0085] S2. The nickel-based alloy powder described in S1 is doped with 2% silicon powder, placed in a planetary ball mill, and ball-milled for 80 minutes without adding grinding balls during the ball milling process to obtain a nickel-based alloy composite powder for standby use; the sphericity of the silicon powder is ≥80%, the particle size distribution is 5-15μm, the median particle size is 8-10μm, and the fluidity is 25s / 50g;

[0086] S3. Place the No. 45 steel plate in the forming bin, grind the surface of the steel plate flat, and wipe it clean with alcohol; add the mixed nickel-based alloy composite powder into the powder bin, preheat it at 240°C, and use 3D printing to prepare the nickel-based alloy composite powder described in S2 to obtain the target. The process parameters of 3D printing are as follows: laser power is 400W, scanning speed is 850mm / s, powder thickness is 50μm, and after 3D printing, annealing treatment is carried out at 780°C for 150min, and then cooled in the furnace to obtain the composite nickel-based alloy microchannel.

[0087] Compared with Example 1, the main difference of this example is that the annealing treatment in step S3 is carried out at 780° C. for 150 min.

[0088] Comparative Example 1

[0089] A method for preparing a composite nickel-based alloy microchannel, wherein the steps not specifically described are the same as those in Example 1, except that:

[0090] Compared with Example 1, the doping amount of silicon powder in step S2 of this comparative example is 5%.

[0091] Comparative Example 2

[0092] A method for preparing a composite nickel-based alloy microchannel, wherein the steps not specifically described are the same as those in Example 1, except that:

[0093] Compared with Example 1, the doping amount of silicon powder in step S2 of this comparative example is 6%.

[0094] Comparative Example 3

[0095] A method for preparing a composite nickel-based alloy microchannel, wherein the steps not specifically described are the same as those in Example 1, except that:

[0096] Compared with Example 1, the particle size of the silicon powder in step S2 of this comparative example is 15-53 μm, and the sphericity is less than 80%.

[0097] Comparative Example 4

[0098] A method for preparing a composite nickel-based alloy microchannel, wherein the steps not specifically described are the same as those in Example 1, except that:

[0099] Compared with Example 1, the particle size of the silicon powder in step S2 of this comparative example is 15-53 μm, and the sphericity is less than 60%.

[0100] Comparative Example 5

[0101] A method for preparing a composite nickel-based alloy microchannel, wherein the steps not specifically described are the same as those in Example 1, except that:

[0102] Compared with Example 1, grinding balls were added during the ball milling process in step S2 of this comparative example.

[0103] Comparative Example 6

[0104] A method for preparing a composite nickel-based alloy microchannel, wherein the steps not specifically described are the same as those in Example 1, except that:

[0105] Compared with Example 1, the 3D printing scanning speed in step S3 of this comparative example is 500 mm / s.

[0106] Comparative Example 7

[0107] A method for preparing a composite nickel-based alloy microchannel, wherein the steps not specifically described are the same as those in Example 1, except that:

[0108] Compared with Example 1, the 3D printing scanning speed in step S3 of this comparative example is 1200 mm / s.

[0109] Comparative Example 8

[0110] A method for preparing a composite nickel-based alloy microchannel, wherein the steps not specifically described are the same as those in Example 1, except that:

[0111] Compared with Example 1, no annealing treatment is performed in step S3 of this comparative example.

[0112] Comparative Example 9

[0113] A method for preparing a composite nickel-based alloy microchannel, wherein the steps not specifically described are the same as those in Example 1, except that:

[0114] Compared with Example 1, the step S3 of this comparative example does not perform furnace cooling.

[0115] The composite nickel-based alloy microchannel of Example 1 was characterized and analyzed, and the results are as follows:

[0116] The microstructure of the composite nickel-based alloy microchannel obtained in this embodiment is shown in FIG. Figure 1 As shown. Figure 1 It can be seen that the composite nickel-based alloy microchannel obtained in this embodiment is well formed, relatively flat, has no cracks and has a dense structure with a density of 99.9% and no unmelted particles.

[0117] like Figure 2 As shown, the composite nickel-based alloy sample prepared by the method for preparing the composite nickel-based alloy microchannel of the present application has a good macroscopic shape, a relatively flat surface and no cracks.

[0118] like Figure 3 As shown, the microstructure of the composite nickel-based alloy microchannel obtained in this embodiment was immersed in a mixed solution of nitric acid and sulfuric acid at 50°C for 90 days, and the corrosion resistance was 0.0143 mm / a. The corrosion resistance of the sample was better than that of the Hastelloy material.

[0119] like Figure 4 As shown, the composite nickel-based alloy microchannel sample obtained in this embodiment has excellent forming quality, a smooth surface and no cracks.

[0120] The test results of the other embodiments are basically consistent with it. Specifically shown in Table 1 below:

[0121] Table 1 Test data of composite nickel-based alloy microchannels in Examples 2-7

[0122]

[0123] The performance tests of Comparative Examples 1-9 were carried out using the same testing method as Example 1.

[0124] The results are shown in Table 2 below:

[0125] Table 2 Comparative Examples 1-9 Composite Nickel-Based Alloy Microchannel Performance Test Results

[0126]

[0127]

[0128] As can be seen from the above table, each embodiment of the present invention has high density, good corrosion resistance and good molding quality, no deformation and cracks, and can effectively avoid the problems of poor corrosion resistance and poor molding quality of existing technologies and materials. However, in Comparative Examples 1 and 2, the silicon powder doping amount exceeds the range, breaking the balance of alloy elements and generating cracks; in Comparative Example 3, the silicon powder particle size is too large, making it difficult to form a good eutectic structure, and the molding quality is poor; in Comparative Example 4, the silicon powder particle size is too large, the sphericity is too small, and the molding quality is poor; in Comparative Example 5, grinding balls are added during the ball milling process, resulting in the mixed silicon powder breaking into nanopowder and failing to form; in Comparative Examples 6 and 7, the laser parameters exceed the range and there are many surface defects; in Comparative Example 8, no annealing treatment is performed, the stress is large, resulting in deformation on the surface; in Comparative Example 9, no furnace cooling is performed, and there are cracks.

[0129] In summary, the present invention obtains a composite nickel-based alloy microchannel by compounding a nickel-based alloy with a silicon element, and improves the hardness and strength of the composite nickel-based alloy microchannel through the synergistic effect of Cr, Mo, Mn, W, Ni and Si elements, and effectively improves the acid corrosion resistance of the nickel-based alloy. The silicon element is doped into the composite nickel-based alloy microchannel by the operation of doping silicon powder alone, so that the silicon element is dissolved into the grains as little as possible during the printing process, and most of it is retained in the grain boundary in the form of eutectic, reducing the generation of cracks, and then the silicon element is uniformly diffused to the entire composite nickel-based alloy microchannel by heat treatment, so as to comprehensively enhance the corrosion resistance, and obtain a composite nickel-based alloy microchannel with excellent forming quality and good corrosion resistance. The 3D printing molding quality is excellent, there is no crack, the density is high, and there are few pores, which can effectively avoid the cracks and pores caused by the printing quality. At the same time, the heat treatment makes the distribution of each element more uniform, effectively avoiding the problem of pitting corrosion, and the corrosion resistance is further improved. It can be used for microreactor equipment in acidic corrosion environment, and has broad economic value in the future.

[0130] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a composite nickel-based alloy microchannel, characterized in that: The following steps are involved: S1. Prepare a nickel-based alloy powder, comprising the following elements by mass percentage: Cr: 15-20%, Mo: 16-20%, Mn: 0.5-1%, W: 2-3%, Ni: 54-62.5%, for standby use; S2. The nickel-based alloy powder is doped with 2-3% silicon powder in S1, and the mixture is ball-milled without adding grinding balls during the ball milling process to obtain a nickel-based alloy composite powder for use; S3. Preheating, using 3D printing to prepare the nickel-based alloy composite powder of S2 to obtain the target, annealing at 600-780°C, and cooling with the furnace to obtain the composite nickel-based alloy microchannel; The particle size of the nickel-based alloy powder in S1 is 15-53 μm, and the sphericity is ≥ 90%. The particle size of the silicon powder in S2 is 5-15 μm, and the sphericity is ≥ 80%. S3 The 3D printing laser power is 250-450w, the speed is 600-1000mm / s, and the powder thickness is 40-60μm.

2. A method for preparing a composite nickel-based alloy microchannel according to claim 1, characterized in that: The nickel-based alloy powder described in S1 has a median particle size of 30-35 μm and a fluidity of 15-20 s / 50 g.

3. A method for preparing a composite nickel-based alloy microchannel according to claim 1, characterized in that: The median particle size of the silicon powder S2 is about 8-10 μm, and the fluidity is 15-30s / 50g.

4. A method for preparing a composite nickel-based alloy microchannel according to claim 1, characterized in that: S2 The ball milling mixing time is 60-180 min.

5. A method for preparing a composite nickel-based alloy microchannel according to claim 1, characterized in that: S3 The 3D printing described above is to deposit the above-mentioned nickel-based alloy composite powder on a steel plate by using a 3D printing method.

6. A method for preparing a composite nickel-based alloy microchannel according to claim 1, characterized in that: The preheating temperature in S3 is 200-300°C.

7. A method for preparing a composite nickel-based alloy microchannel according to claim 1, characterized in that: The annealing treatment in S3 is carried out at 600-780°C for 60-240 minutes.

8. A composite nickel-based alloy microchannel, characterized in that: The composite nickel-based alloy microchannel is prepared by the preparation method of any one of claims 1 to 7.

9. A composite nickel-based alloy microchannel according to claim 8, characterized in that: The microchannel has an FCC phase.

10. A composite nickel-based alloy microchannel according to claim 8, characterized in that: The microchannel has an elliptical series structure.

Citation Information

Patent Citations

  • High-sphericity Inconel 625 alloy powder and preparation method and application thereof

    CN105149603A

  • Forming method of ceramic microchannel, ceramic microchannel material and application

    CN113956052A

  • High-hardness corrosion-resistant nickel-aluminum bronze welding wire, preparation method thereof and application of high-hardness corrosion-resistant nickel-aluminum bronze welding wire in alloy cladding

    CN115537596A

  • Iron-element-free low-melting-point nickel-based alloy coating and preparation method thereof

    CN117702101A

  • Method for preparing surface modified nickel-based alloys

    KR1020110130929A